Repurposing Nintedanib for pathological cardiac remodeling and dysfunction. (July 2021) - Umbarkar, Prachi; Singh, Anand P.; Tousif, Sultan; Zhang, Qinkun; Sethu, Palaniappan; Lal, Hind
Abstract: Heart Failure (HF) is the leading cause of death worldwide. Myocardial fibrosis, one of the clinical manifestations implicated in almost every form of heart disease, contributes significantly to HF development. However, there is no approved drug specifically designed to target cardiac fibrosis. Nintedanib (NTB) is an FDA approved tyrosine kinase inhibitor for idiopathic pulmonary fibrosis (IPF) and chronic fibrosing interstitial lung diseases (ILD). The favorable clinical outcome of NTB in IPF patients is well established. Furthermore, NTB is well tolerated in IPF patients irrespective of cardiovascular comorbidities. However, there is a lack of direct evidence to support the therapeutic efficacy and safety of NTB in cardiac diseases. In this study we examined the effects of NTB treatment on cardiac fibrosis and dysfunction using a murine model of HF. Specifically, 10 weeks old C57BL/6J male mice were subjected to Transverse Aortic Constriction (TAC) surgery. NTB was administered once daily by oral gavage (50 mg/kg) till 16 weeks post-TAC. Cardiac function was monitored by serial echocardiography. Histological analysis and morphometric studies were performed at 16 weeks post-TAC. In the control group, systolic dysfunction started developing from 4 weeks post-surgery and progressed till 16 weeks. However, NTB treatment prevented TAC-induced cardiac functional decline. In another experiment, NTB treatment was stopped at 8 weeks, and animals were followed till 16 weeks post-TAC. Surprisingly, NTB's beneficial effect on cardiac function was maintained even after treatment interruption. NTB treatment remarkably reduced cardiac fibrosis as confirmed by Masson's trichrome staining and decreased expression of collagen genes (COL1A1, COL3A1). Compared to the TAC group, NTB treated mice showed a lower HW/TL ratio and cardiomyocyte cross-sectional area. NTB treatment reduced myocardial and systemic inflammation by inhibiting pro-inflammatory subsets and promoting regulatory T cells (Tregs). Our in vitro studies demonstrated that NTB prevents myofibroblast transformation, TGFβ1-induced SMAD3 phosphorylation, and the production of fibrogenic proteins (Fibronectin-1, α-SMA). However, NTB promoted immunosuppressive phenotype in Tregs, and altered vital signaling pathways in isolated cardiac fibroblast and cardiomyocytes, suggesting that its biological effect and underlying cardiac protection mechanisms are not limited to fibroblast and fibrosis alone. Our findings provide a proof of concept for repurposing NTB to combat adverse myocardial fibrosis and encourage the need for further validation in large animal models and subsequent clinical development for HF patients. Graphical Abstract: ga1